1980
DOI: 10.1093/ajcp/73.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Legionnaires’ Disease: Postmortem Pathologic Findings of 20 Cases

Abstract: From March 1977 to December 1978, postmortem examination was performed at Wadsworth Veterans Administration Medical Center for 20 patients who had had nosocomially acquired Legionnaires' disease. Seventeen patients died during the acute illness due to Legionnaires' disease, and three patients died after clinical resolution of the acute process. The only consistent postmortem findings were limited to the lungs. Confluent bronchopneumonia, and less frequently lobar pneumonia, was present in most cases. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“…In contrast, PMN stimulated with leukotriene B 4 (LTB 4 ) or IL-8 form zones of loose apposition on fibrin and migrate effectively into these gels. In addition, fMLP or TNF-␣ inhibited PMN migration through fibrin gels in response to LTB 4 or IL-8. These findings suggested that fMLP might exert an inhibitory effect on PMN killing of bacteria at sites of fibrin deposition by blocking PMN migration into and in these sites.…”
Section: T He Cellular Mechanisms Used By Neutrophils (Polymorphonuclmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, PMN stimulated with leukotriene B 4 (LTB 4 ) or IL-8 form zones of loose apposition on fibrin and migrate effectively into these gels. In addition, fMLP or TNF-␣ inhibited PMN migration through fibrin gels in response to LTB 4 or IL-8. These findings suggested that fMLP might exert an inhibitory effect on PMN killing of bacteria at sites of fibrin deposition by blocking PMN migration into and in these sites.…”
Section: T He Cellular Mechanisms Used By Neutrophils (Polymorphonuclmentioning
confidence: 94%
“…Following wounding or invasion of tissues by bacteria, fibrinogen-rich exudates lead to the formation of fibrin gels to which bacteria bind or in which they become embedded (3,4). Fibrin also is deposited on prosthetic devices such as venous catheters, making them attractive substrates for adhesins expressed by Staphylococci and other bacteria (5).…”
Section: T He Cellular Mechanisms Used By Neutrophils (Polymorphonuclmentioning
confidence: 99%
“…Radiation-primed organising pneumonia is thus quite similar to COP. Interestingly, this peculiar iatrogenic organising pneumonia provides some insight into the pathogenesis of Chlamydia pneumoniae [184,185] Coxiella burnetii [186,187] Legionella pneumophila [95,[188][189][190][191][192][193][194] Mycoplasma pneumoniae [95,189,[195][196][197] Nocardia asteroides [198,199] Pseudomonas aeruginosa [200] Serratia marcescens [201]; in lung transplant recipient [200] Staphylococcus aureus In lung transplant recipient [200] Streptococcus pneumoniae [5,6,202] Viruses Adenovirus [203] Cytomegalovirus [203,204] Herpes virus In lung transplant recipient [200] HIV [205][206][207][208][209][210]; in a pregnant patient using cocaine [205]; following highly active antiretroviral therapy introduction [211] Influenza virus [189,[212][213][214] Parainfluenza virus [215] Human herpes virus-7 …”
Section: Determined Causes Of Organising Pneumoniamentioning
confidence: 99%
“…The clinical features of Legionnaires' disease (LD) range from an asymptomatic course to fatal pneumonia. Although there have been no properly controlled studies of prolonged sequelae, a few case reports have noted a permanent pulmonary sequelae including pulmonary fibrosis following LD (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%